Chinese vocabulary and elements of culture reflected in the lexical meaning as a challenge in the teaching of Chinese as a foreign language - Zhu, Zhiping (Lingua Posnaniensis, 2020)
This paper describes the elements of Chinese culture enclosed in vocabulary and in the meaning of words; it is divided into four parts. Firstly, it is pointed out that, due to the fact that words are written down with Chinese characters, teachers of Chinese should purposefully help the students understand the rich culture contained in Chinese words, especially disyllabic compounds. Secondly, the article presents the investigation methods concerning compound words applied by the researchers of Chinese lexicon；It also assesses their applicability with regard to teaching a second language. Thirdly, the paper discusses five ways of incorporating Chinese culture during the process of formation of compound words, and points out their relationship with second language teaching. Finally, the paper discusses the methods applied in teaching Chinese vocabulary, and puts forward two methods of teaching vocabulary and their strategies at different levels.